Floral phenology and floral induction in Leptospermum scoparium. Issue 4 (2nd October 2018) - Bicknell, Ross; Jaksons, Peter
ABSTRACT: Leptospermum scoparium is a species found throughout New Zealand and southeastern Australia. It typically flowers in the spring and early summer, although occasional flowers can often be seen on plants throughout the year. A study of bud phenology revealed that floral bract primordia initiated development at apices of sub-terminal branches soon after the longest day, and that floral bud development progressed throughout the summer, autumn and winter months. Flower bud opening then occurred the following spring with the resumption of vegetative growth. A controlled environment study indicated that L. scoparium acted as a 'short day plant'. When plants were maintained under a 16 h photoperiod (16 h of light and 8 h of dark per day) they remained vegetative. Shorter photoperiods were then tested and values less than 11.5 h were found to be inductive for the two varieties tested ('Crimson Glory' and 'Nanum Ruru'). Plants needed to be subjected to this treatment for at least 4 weeks before induction was observed. An interaction with temperature was also detected. Plants were induced to flower by a 9.5 h photoperiod administered at a constant 20 °C but either failed to flower, or did so very poorly when the 9.5 h photoperiod was administered at a constant 10 °C.